Effects of a Novel Bovine Lactoferrin-Derived Peptide on the Intestinal Morphology and Intestinal Flora in Rats - Tianle Huang; Huan Yang; Yang Zhao; Haiyue Cui; Xiaoxi Qi; Liguang Miao (Microorganisms)
Bovine lactoferrin-derived peptide LF-MQL was administered to healthy rats to assess its effects on growth parameters and gut morphology. Faecal samples were analysed by 16S rRNA high-throughput sequencing to investigate the modulatory effects of LF-MQL on the composition and diversity of the gut microbiota. The results showed that both experimental groups maintained intact intestinal organization. Notably, supplementation with LF-MQL significantly increased the length of small intestinal villi compared to the control group (p < 0.05), and an improvement in the structural organization of the villi, including a more ordered and compact arrangement, was observed. These morphological findings suggest that there are no adverse effects associated with LF-MQL administration. In addition, administration of LF-MQL modulates the functional activity of the gut microbiota and regulates their involvement in host-related metabolic pathways, thereby improving gut homeostasis. These findings provide a theoretical basis for evaluating the safety of bovine lactoferrin peptides in food and pharmaceutical applications.